2018
DOI: 10.1111/ans.14760
|View full text |Cite
|
Sign up to set email alerts
|

Fournier's gangrene: not as lethal as previously thought? A case series

Abstract: While a prolonged admission and multiple operations are expected, early diagnosis and aggressive multimodal treatment may result in a significantly better survival outcome than those quoted in previous literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 7 publications
1
14
1
3
Order By: Relevance
“…Fournier's gangrene is known to be a rapid onset disease, but studies have shown that application to the hospital is delayed by an average of one week after initial symptoms have presented. [13] In our study, the median time from symptom onset to hospital application was four (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) days. Immediate diagnosis and treatment of FG are known to affect prognosis.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Fournier's gangrene is known to be a rapid onset disease, but studies have shown that application to the hospital is delayed by an average of one week after initial symptoms have presented. [13] In our study, the median time from symptom onset to hospital application was four (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) days. Immediate diagnosis and treatment of FG are known to affect prognosis.…”
Section: Discussionmentioning
confidence: 64%
“…The age of the patients hospitalized in the intensive care unit (ICU) was found to be higher than the patients who did not require ICU admittance (65.33±11.63 years vs. 54.39±11.79 years, respectively; p=0.013). Median FGSI score was 2 (0-14), while the median UFGSI score was 4 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Median FGSI and UFGSI scores were found to be higher in patients accepted to the ICU compared to those who were not (4 vs. 2, p=0.025; and 6 vs. 3, p=0.002, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fournier's gangrene is a rare but feared necrotizing fasciitis of the genitals and perineum associated with significant morbidity and mortality between 7% and 40% 1–3 . It is a polymicrobial infection spreading along subcutaneous and fascial planes 2 .…”
Section: Figurementioning
confidence: 99%
“…Fournier's gangrene is a rare but feared necrotizing fasciitis of the genitals and perineum associated with significant morbidity and mortality between 7% and 40%. [1][2][3] It is a polymicrobial infection spreading along subcutaneous and fascial planes. 2 Clinically, it can be difficult to diagnose, but due to its rapid progression, and requires immediate and aggressive surgical debridement.…”
mentioning
confidence: 99%